Automated process for analyzing 2D CAD floor plan drawings and generating FloorspaceJS-compatible space objects for building energy simulations - Wei-Jen Chen; Min-Cheng Tu (Results in Engineering)
Building energy simulation has been widely utilized to support the design decision-making process for new constructions and to establish baselines for energy retrofitting of existing buildings. However, the requirement for well-trained engineers to spend substantial time completing the work has somewhat hindered its development. This paper attempts to extract geometric data from existing 2D floor plan drawings and then proposes an algorithm to identify all faces enclosed by simple closed curves on the drawings. These faces are subsequently converted into the FloorspaceJS format files supported by the OpenStudio Application, which can be directly imported for further processing. The results indicate that the time complexity of this process, represented using Big O notation to describe the upper bound of algorithmic runtime in computational complexity analysis, is O(NM), where N represents the total number of vertices and M represents the total number of line segments in the relevant layer of the drawing. Given that N and M are typically within manageable limits, the algorithm is expected to complete its task in seconds. As a result, this approach is well-suited to accelerating building energy simulation, thereby saving engineers valuable time.